Early Events in Chikungunya Virus Infection—From Virus Cell Binding to Membrane Fusion - van Duijl-Richter, Mareike K. S. (Viruses, 2015)
Chikungunya virus (CHIKV) is a rapidly emerging mosquito-borne alphavirus causing millions of infections in the tropical and subtropical regions of the world. CHIKV infection often leads to an acute self-limited febrile illness with debilitating myalgia and arthralgia. A potential long-term complication of CHIKV infection is severe joint pain, which can last for months to years. There are no vaccines or specific therapeutics available to prevent or treat infection. This review describes the critical steps in CHIKV cell entry. We summarize the latest studies on the virus-cell tropism, virus-receptor binding, internalization, membrane fusion and review the molecules and compounds that have been described to interfere with virus cell entry. The aim of the review is to give the reader a state-of-the-art overview on CHIKV cell entry and to provide an outlook on potential new avenues in CHIKV research.